2020
DOI: 10.1002/adma.201906064
|View full text |Cite
|
Sign up to set email alerts
|

Photoactivated Artificial Molecular Machines that Can Perform Tasks

Abstract: The ORCID identification number(s) for the author(s) of this article can be found under https://doi.org/10.1002/adma.201906064.Research on artificial photoactivated molecular machines has moved in recent years from a basic scientific endeavor toward a more applicative effort. Nowadays, the prospect of reproducing the operation of natural nanomachines with artificial counterparts is no longer a dream but a concrete possibility. The progress toward the construction of molecular-machinebased devices and materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
78
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(79 citation statements)
references
References 113 publications
(169 reference statements)
0
78
0
1
Order By: Relevance
“…The macroscopic amplification of a collection of stimuli-responsive molecular switches/machines is a common challenge that has attracted widespread interest in the past decades. [56][57][58][59][60] Several strategies have been proved to be reliable with some photoswitches and molecular machines by covalently incorporating stimuliresponsive molecular units into polymeric networks, such as liquid crystal (LC) elastomers and multi-branch-crosslinked gels. [61][62][63] Giuseppone and co-workers, in a pioneering study, demonstrated that covalently crosslinked motorized gels can perform light-driven macroscopic volume shrinkage due to the intertwining of polymer chains as a result of the light-driven unidirectional rotation of motors.…”
Section: Hierarchically Supramolecular Amplificationmentioning
confidence: 99%
See 1 more Smart Citation
“…The macroscopic amplification of a collection of stimuli-responsive molecular switches/machines is a common challenge that has attracted widespread interest in the past decades. [56][57][58][59][60] Several strategies have been proved to be reliable with some photoswitches and molecular machines by covalently incorporating stimuliresponsive molecular units into polymeric networks, such as liquid crystal (LC) elastomers and multi-branch-crosslinked gels. [61][62][63] Giuseppone and co-workers, in a pioneering study, demonstrated that covalently crosslinked motorized gels can perform light-driven macroscopic volume shrinkage due to the intertwining of polymer chains as a result of the light-driven unidirectional rotation of motors.…”
Section: Hierarchically Supramolecular Amplificationmentioning
confidence: 99%
“…This model can be considered to be a ''macroscopic supramolecular machine.'' 56,58 This concept of signal delivery from molecular motors to macroscopic materials can create a new generation of smart materials whose responsiveness originates at the molecular level.…”
Section: Hierarchically Supramolecular Amplificationmentioning
confidence: 99%
“…Generally, switches can be divided into three groups: [2] molecular switch (e. g., pH indicators), supramolecular switches (e. g., pseudorotaxanes) and mechanically interlocked molecular (MIM) switches (e. g., rotaxanes) [3] . The term “molecular switch” originated in the early 1980s and was first used in biological field [4] .…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that rotaxane-type systems can control the shuttle process by photoinduced conformational transformation of the photoswitch moieties. [16][17][18][19] If this lightcontrolled shuttling can be incorporated into the rotaxane transporter operated by our reported shuttle mechanism, [11a] it will be possible to realize light-gated ion transport across lipid membranes. As illustrated in Scheme 1, an azobenzene-based molecular shuttle (PR2, Scheme 1 a) was designed, which includes an azobenzene-modified amphiphilic thread (PT2) with two secondary ammonium ions as the terminal stations for the shuttle and a wheel (RCE) consisting of a K + selective receptor, i.e., a benzo [18]crown-6 (B18C6) ring.…”
mentioning
confidence: 99%